Penerapan Teknologi dalam Pembelajaran Kelas 6 SDN Wates 2 Sesuai dengan Landasan Ilmiah dan Teknologi - Choirudin Lutfi Triaji (Educational Consultant & Counseling Career (EC3) Mataram, 2024)
Technological developments are currently growing rapidly, especially in the field of education. Elementary schools as the foundation of education are expected to be able to make good use of these technological developments. Technology in schools is present in learning. Scientific and technological foundations as the basis for conveying knowledge by teachers that can be supported by technology. Elementary Schools of Wates 2 has excellent facilities for the use of technology in learning. This research aims to analyze the application of technology in learning at Elementary Schools of Wates 2, Mojokerto City, especially grade 6 and its conformity with scientific and technological foundations. Class six learning at Elementary Schools of Wates 2 is carried out using several technologies in utilizing products which are available at simple to high levels as well as in the learning process carried out. Student in grade 6 at Elementary Schools of Wates 2, learning technology is also in the design, development, utilization, management and assessment stages of learning resources and processes. Learning is carried out according to a scientific basis which is based on the types of scientific foundations of education. The existing learning also provides an understanding of how technology can influence the way students learn and the way educators teach in grade 6 at Elementary Schools of Wates 2.